Issues of Sustainability in Agricultural Training - Királyné Kiszely , Éva Anikó; Bakos, Izabella Mária (Acta Carolus Robertus, 2023)
The education system has an important role and responsibility in educating the future generation, to become conscious consumers. Environmental awareness appears on several levels in their way of life and lifestyle, which is greatly influenced by the education system.According to the opinion of various world organizations (UN, UNESCO, WHO), education is one of the most effective ways of shaping attitudes within an organized framework and developing individual competencies and skills for becoming a sustainable consumer. (UNESCO 2014, US 2002)One of the aims of this literature summary is to provide a literary overview of how sustainability is presented in education, the other aim is to shed light on the presentation of sustainability dimensions - in vocational agricultural training - by presenting an effective, foreign, food industry model. Encouraging the young generation to achieve comprehensive actions towards global sustainability goals in economic life and society is important, therefore it is necessary to develop an applicable methodology.
Keywords: sustainability development; environmental awareness; vocational training; food industry education; competence